Production Process of Hydrolysate from Steam Explosion of Oil Palm Trunk for Xylitol Fermentation - Pitchaya Pumiput,; Sawitri Chuntranuluck,; Vichien Kitpreechavanich,; Vittaya Punsuvon,; Pilanee Vaithanomsat, (Agriculture and Natural Resources, 2008)
The steam-exploded hemicellulose hydrolysate of 100 g oil palm trunk chips was acid posthydrolysed under the condition of autoclaving at 120 °C with 1%w/v H2SO4 for 30 min. The highest amounts of xylose and glucose obtained were 8.15 g and 2.46 g, respectively. The optimal adsorption condition to remove toxic compounds in hemicellulosic hydrolysate was achieved in two steps. Five percents (w/v) of activated carbon were used in the first step for 30 min then 2% (w/v) activated carbon were used in the second step for 60 min. The comparisons were made between two sources of fermentation media, hydrolysate and pure xylose. It was found that fermentation of the hydrolysate with Candida magnolia TISTR 5664 gave xylitol at 0.08 g Yp/s of xylitol/g of xylose whereas fermentation of pure xylose gave xylitol at 0.29 g Yp/s of xylitol/g. The fermentation with C. guilliermondii FTI 20037 from the hydrolysate gave xylitol at 0.12 g Yp/s of xylitol/g of xylose whereas the fermentation from pure xylose gave xylitol at 0.30 g Yp/s of xylitol/g of xylose.